DENSIO-VISCOMETRIC STUDIES OF TIO2-MCM-41 IN ETHANOLIC NICOTINAMIDE SOLUTIONS AND ITS APPLICATION IN DRUG DELIVERY OF IBUPROFEN - Swagatika, Srabani; Dinda, Agnimitra; Dash, Suresh Kumar; Dash, Upendra Nath (International Journal of Pharmacy and Pharmaceutical Sciences, 2015)
Objective: To study the density, viscosity of the solutions of TiO2-MCM-41 in the presence of nicotinamide as hydrotropic agent in ethanol solvent at different temperatures ranging from 298.15K to 313.15K at an interval of 5K, and its application as a drug delivery system. Methods: 10 and 15 weight percentages of TiO2-MCM-41 were synthesized via co-condensation method using cetyl hexadecyltrimethyl ammonium bromide (CTAB) as structure directing agent, tetraethylorthosilicate(TEOS) as silica source and Degussa P-25 as titania source. The characterization of the prepared samples was done by powdered XRD, Fourier Transformed-Infrared spectroscopy (FTIR), scanning electron microscopy (SEM), and DSC. Its drug delivery activity was also studied taking Ibuprofen as test drug. Results: Characterization result indicated that TiO2-MCM-41 retained the mesoscopic morphology and porous structure. The results of density and viscosity measurements have been discussed in the light of molecular interactions. It was found that TiO2-MCM-41 have lower density and viscosity in comparison to parent MCM-41, whereas (15)TiO2-MCM-41 shows highest solute-solvent interaction and lowest solute-solute interaction in ethanol in presence of nicotinamide and exhibited highest drug release capacity.